Association between LH receptor regulation and ovarian hyperstimulation syndrome in a rodent model. Issue 2 (August 2020) - Zheng, Cuihong; Gulappa, Thippeswamy; Menon, Bindu; Menon, K M J
Abstract : Ovarian hyperstimulation syndrome (OHSS) is a common complication of ovarian stimulation associated with the administration of human chorionic gonadotropin (hCG) during assisted reproduction. We have determined the expression of luteinizing hormone receptor ( Lhcgr ) mRNA, vascular endothelial growth factor (VEGF), and its transcription factor, HIF1α, during the periovulatory period in a rodent model of OHSS and compared these results with normal ovulatory periods. These results showed that the downregulation of Lhcgr mRNA in response to conditions that mimic preovulatory LH surge was significantly impaired in the OHSS group compared to the complete downregulation seen in the control group. Most importantly, the downregulation of luteinizing hormone receptor mRNA expression following hCG administration was sustained in the control group up to 48 h, whereas it remained at significantly higher levels in the OHSS group. This impairment of hCG-induced Lhcgr downregulation in the OHSS group was accompanied by significantly elevated levels of VEGF and its transcription factor, HIF1α. Furthermore, the downregulation of Lhcgr that occurs in response to a preovulatory LH surge in normal cycles was accompanied by low levels of VEGF. This study shows that, while downregulation of Lhcgr as well as low VEGF levels are seen in response to a preovulatory LH surge in normal ovarian cycle, impaired Lhcgr downregulation and elevated VEGF levels were found in the OHSS group.